P3.102 HIV Risk in People Who Inject Different Drugs: Systematic Review and Meta-Analysis. (13th July 2013) - Tavitian-Exley, I; Boily, M C; Vickerman, P
Abstract : Objective: To compare and understand how the risk of HIV infection in people who inject drugs (PWID) varies by substances and regions. Methods: A systematic review and meta-analysis was conducted. EMBASE and Medline were searched to identify cohort studies on HIV incidence in PWID injecting different drugs. HIV incidence rate ratio (IRR) was used to compare risk between drug injectors and non injectors, when possible, or study participants not injecting that substance, otherwise. Pooled estimates of unadjusted IRR (uIRR) were derived using random effects models. Sub-group analyses by substance and region were conducted and sources of uIRR variations explored. Results: Eleven cohort studies were included of 3, 941 studies screened. HIV incidence by substance was reported for injecting cocaine (8 in Canada, America, Europe), amphetamine-type stimulants (ATS) (5 in Europe, Eastern Europe, Asia), heroin (9 in all regions), opiates and stimulants in (4 in America, Europe, Eastern Europe) and opiates and sedatives (4 in Europe, Asia). HIV risk for cocaine injectors was 3.5 times greater than non injectors (pooled uIRR = 3.5, 95% CI: 2.9–4.3) with increased sexual and injecting risk behaviours reported by cocaine-, compared to non-cocaine injectors in North America. HIV risk for heroin injectors was almost twice (pooled uIRR = 1.5, 95% CI: 1.4–1.6) that of non- injectors in North America and four times (pooled uIRR = 4.0, 95% CI: 3.2–5.0) in Europe and Asia, respectively. ATS yielded a pooled uIRR of 2.7 (95% CI: 2.2–3.5) for Europe and Asia. Conclusion: Variations in the risk of HIV seroconversion found among injectors of different drugs suggest that specific substances influence different behavioural and biological infection pathways. Results support previous findings in Canada and America, that injecting cocaine carries the highest HIV risk. HIV risk across drugs by regions require further exploration. Substances injected should be considered in harm reduction and sexual risk reduction strengthened